2019
DOI: 10.17650/1726-9776-2019-15-1-57-65
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of tumor PD-L1 status in patients with metastatic prostate cancer

Abstract: Одним из потенциальных биомаркеров для больных метастатическим гормоночувствительным раком предстательной железы (РПЖ) может быть определение экспрессии лиганда белка программируемой клеточной гибели (PD-L1) в опухоли, ассоциированной с неблагоприятными результатами лечения и снижением выживаемости больных раком поджелудочной железы, легкого и другими злокачественными новообразованиями. Цель исследования -оценка прогностической значимости положительного статуса PD-L1(+) опухоли на время до развития кастрационн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…In a smaller series (n = 45), the median MFS was shorter in PD-L1+ patients (49 vs. 68 months; p = 0.090): multivariate analysis confirmed the independent predictive value of expression and hyperexpression of PD-L1 in tumor cells for MFS (p = 0.025, p = 0.032) and CSS (p = 0.097, p = 0.065) [38].…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In a smaller series (n = 45), the median MFS was shorter in PD-L1+ patients (49 vs. 68 months; p = 0.090): multivariate analysis confirmed the independent predictive value of expression and hyperexpression of PD-L1 in tumor cells for MFS (p = 0.025, p = 0.032) and CSS (p = 0.097, p = 0.065) [38].…”
mentioning
confidence: 69%
“…The positivity rate of PD-L1 seemed higher in CRPCs (440/904, 49%) [8,9,13,17,21,27,35,38,50,55,59,62,66,74,90,92,[98][99][100] as compared to hormone-sensitive PCs (44/254, 17%): PD-L1 was usually tested on primary tumors that probably had not yet undergone hormonal therapy as this information was not always available [27,32,35,39].…”
Section: Pd-l1 Expression and Treatmentmentioning
confidence: 99%
“…We found that 29% of acinar PCs, 7% of ductal PCs, and 46% of neuroendocrine carcinomas or tumors were classified as PD-L1-positive by immunohistochemical analysis on tumor tissue, despite these results may be influenced by some selection biases [8,9,[11][12][13]17,21,27,29,32,[35][36][37][38][39][41][42][43][44][50][51][52][53][54][55]57,[59][60][61][62]66,67,74,75,[77][78][79][83][84][85]89,90,[92][93][94][98][99][100]111,…”
Section: Discussionmentioning
confidence: 99%
“…1369/4708 (29%) PCs were overall classified as positive but different antibody clones, scoring systems, and/or cut-offs for positivity were used, with a range as wide as 0-100% in single studies. 687/2676 (26%) cases were considered PD-L1-positive if at least ≥1% of tumor cells were stained [8,13,27,29,[35][36][37][38][39][41][42][43]54,62,66,67,74,75,[77][78][79]84], while 93/1062 (9%) PCs were counted as positive for ≥5% of stained tumor cells [17,39,43,57,66,94,[98][99][100]120]. 9/523 (2%) cases expressed PD-L1 on >50% of tumor cells [66,92], while Wang et al used a cut-off of ≥25% (0/21, 0%) [61].…”
Section: Pd-l1 Immunohistochemical Expression In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation